2018
DOI: 10.21273/hortsci12643-17
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response, Mineral Nutrition, and Water Utilization of Container-grown Woody Ornamentals Grown in Biochar-amended Pine Bark

Abstract: Container-grown nursery crops generally require daily irrigation applications and potentially more frequent applications during the hottest part of the growing season. Developing management practices that make more efficient use of irrigation water is important for improving the sustainability of nursery crop production. Biochar, a byproduct of pyrolysis, can potentially increase the water-holding capacity and reduce water and nutrient leaching. In addition, the development of sensor-based irrigation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The biochars made from different feedstocks could have different physical and chemical properties, which should be taken into account when they are incorporated in containers. Sugarcane bagasse z 343 n n n 0.11 5.8 n n n n n n n n n n [48] Sugarcane bagasse z 343 n n n 0.11 6.1 n n n n n n n n n n [48] Switchgrass z 1000 n n n 0.10 10.8 3.5 n 1.3 79.0 1.20 6.60 n n n n [69] Wheat straw 600 n n n 0.31 10.0 1.0 n 1.0 79.3 n n n n n n [70] Wheat straw n n n n 0.24 9.5 2.5 n n n 0.003 0.10 0.002 0.004 0.0009 n [5] Note: Production temp: production temperature; CC: container capacity; AS: air space; TP: total porosity; BD: bulk density; EC: electrical conductivity; CEC: cation exchange capacity. Pyrolysis was the biochar production method, unless indicated otherwise.…”
Section: Biochar Feedstocksmentioning
confidence: 99%
“…The biochars made from different feedstocks could have different physical and chemical properties, which should be taken into account when they are incorporated in containers. Sugarcane bagasse z 343 n n n 0.11 5.8 n n n n n n n n n n [48] Sugarcane bagasse z 343 n n n 0.11 6.1 n n n n n n n n n n [48] Switchgrass z 1000 n n n 0.10 10.8 3.5 n 1.3 79.0 1.20 6.60 n n n n [69] Wheat straw 600 n n n 0.31 10.0 1.0 n 1.0 79.3 n n n n n n [70] Wheat straw n n n n 0.24 9.5 2.5 n n n 0.003 0.10 0.002 0.004 0.0009 n [5] Note: Production temp: production temperature; CC: container capacity; AS: air space; TP: total porosity; BD: bulk density; EC: electrical conductivity; CEC: cation exchange capacity. Pyrolysis was the biochar production method, unless indicated otherwise.…”
Section: Biochar Feedstocksmentioning
confidence: 99%
“…While less likely to occur with liquid additives, incorporating solid amendments (e.g. biochar, manure, peat, or vermiculite) has been shown to alter substrate physical properties such as bulk density, air space and container capacity (Jacobs et al 2003, Jahromi et al 2018. Thus, any decision to utilize soil additives should take into account the potential impact of these amendments on the physical properties of an existing substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Since humectants such as Hydretaint form strong hydrogen bonds between hydrophilic components of the humectant and water molecules within the substrate matrix, it is possible that these bonds could limit the availability of moisture for absorption by plant roots until, presumably, plant-water potential decreases (becomes more negative), resulting in a directional shift in the water potential gradient. In a study using biochar as a substrate amendment, Jahromi et al (2018) reported that the shoot dry weight of potted hydrangeas (Hydrangea paniculata Siebold) grown in 25% biochar-amended Plants grown from seed in plug trays for 4 weeks prior to transplanting into SP#4 (1L) marketable pots filled with soilless substrate. Transplants allowed to become established for 10 days before beginning the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Coir rates were selected to test a wide percentage range of substrate amendment. Including 10% and 25% coir enabled comparison with results from previous research with biochar [16]. Positive results from other research with 35% coir as a substrate amendment [13,31] supported including higher rates to begin to define the highest rate at which benefits would be derived and provide producers with recommendations.…”
Section: Plant Gas Exchange Parametersmentioning
confidence: 86%
“…In previous studies we used biochar as a substrate amendment and observed its positive effects on increasing water holding capacity, reduction of water and nutrient loss. Biochar amendment affects nutrient concentration and can act as a source of phosphorus and potassium depending on the feedstock type [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%